ANALISIS PENDAPATAN PEDAGANG SAYUR SEBELUM DAN SELAMA MASA PANDEMI COVID-19 DI PASAR LAKESSI KOTA PAREPARE SULAWESI SELATAN (Income Analysis of Vegetable Traders Before And During The Covid-19 Pandemic Period In The Lakessi Market Parepare City, South Sulawesi Province) - Claudya Levirisna Panjaitan; Theodora Katiandagho; Lyndon Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
In early 2020, a new type of pneumonia was found in Wuhan, Hubei Province, which then spread to more than 190 countries and territories. This plague named coronavirus disease 2019 (COVID-19). The spread of this disease has a big impact in social and economic after the policy about social distancing to prevent the virus from spreading. Parepare is one of the cities in South Sulawesi that also affected by the Covid-19 pandemic, This had a big impact in economic of Parepare and one of the most affected are traditional market. This research aims to examine how the covid 19 pandemic affects the demand of vegetables, which is an indicator of profit for vegetable traders, at Lakessi Market, Parepare, South Sulawesi. The sample in this research were 15 traders who only sell vegetables. The method of collection data in this research is interview, and the type of data in this research is qualitative data. The source of data used in this research is primary data and secondary data. The research result is the income of vegetable traders in the Lakkesi market have decreased during the Covid-19 pandemic because the market become more quiet from buyers because of the public's fear of contracting the Covid-19 virus.Keywords: Analysis Income, Vegetable traders, Covid-19 Pandemic, Lakessi Market of Parepare City